KOMPARASI KINERJA KEUANGAN PERBANKAN SYARIAH BERBASIS PENDEKATAN LABA RUGI DAN NILAI TAMBAH - Saifudin, Yulianti; Pribadi, Yayan (IKONOMIKA, 2016)
Abstract-The objectives of this study are to analyze the differences in financial performance of Islamic bank by using the income statement approach and value added approach on financial ratios. Financial ratios used consisted of ROA, ROE, the ratio between the total net income by total earning assets, NPM, and  BOPO. The Object used in this study are listed Islamic Bank at Bank Indonesia. Population of this research are the financial statements of Islamic Banks, while the sample used was the financial statements for 2010-2014 for each income statement and the value added statement.  Analysis tool used to prove the hypothesis of this study is an independent sample t-test.The results showed that the average financial ratio (ROA, ROE, net profit ratio of productive assets, and NPM) there are significant differences between the Income Statement and Value Added Statement, while the BOPO ratio between the Income Statement and the Value Added Statement there is not a difference.